PENGARUH INTEGRITAS, OBJEKTIVITAS DAN KOMPETENSI TERHADAP KINERJA AUDITOR: BUDAYA ORGANISASI SEBAGAI PEMODERASI - Lilis Yulianti; M Rasuli; Vera Oktari (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2020)
This study aims to examine the effect of integrity, objectivity and competence on the auditor's performance. This research is a quantitative research. The population in this study is 47 auditors at the Inspectorate of the Riau Province. The sampling technique used is a saturated sample so that makes all of population as a sample in the study this. The scale of data measurement with a Likert scale. The data are collected through questionnaires that handed directly to the respondens. 41 completed quisioner are receipt and was analysis by WarpPLS 6.0. The results of this study indicate that integrity, objectivity and competence has a direct and significant influence on auditor performance. As well as culture the organization strengthens the influence of integrity, objectivity and competence on auditor performance This shows that the better the integrity, objectivity and applied competencies, it can improve auditor performance